Hydroxymethylnitrofurazone treatment in indeterminate form of chronic Chagas disease: Reduced intensity of tissue parasitism and inflammation—A histopathological study - Scarim, Cauê B. [UNESP]; de Andrade, Cleverton R. [UNESP]; da Rosa, João A. [UNESP]; dos Santos, Jean L. [UNESP]; Chin, Chung M. [UNESP] (Wiley, 2018)
Hydroxymethylnitrofurazone (NFOH) is a nitrofurazone prodrug effective in vivo during acute infections, and it has less hepatotoxicity effect than the standard drug benznidazole (BZN) which has been used during short- and long-term treatment. In the present study, we induced the indeterminate form of Chagas disease in mice with a Y strain of Trypanosoma cruzi and analysed the histopathological data about the effects of NFOH and BZN on different tissues, including the heart, skeletal muscle, liver, kidney, colon, spleen and brain. After infection, BALB/c mice were treated with NFOH (150 mg/kg) and BZN (60 mg/kg) for 60 days and then submitted to immunosuppression using dexamethasone (5 mg/kg) for 14 days. Two trained analysts, as part of a blind evaluation, examined the results using serial sections of 3 mm diameter in two different moments. The results showed reactivation of the disease only in the infected nontreated group (POS). After treatment, amastigote nests were found in the heart, colon, liver and skeletal muscle in the POS group and in the heart and liver of the BZN group. Interestingly, amastigote nests were not found in the NFOH and NEG groups. The histopathological analysis showed fewer tissue lesions and parasite infiltrates in the NFOH group when compared with the BZN and POS groups. We have not observed any increase in the levels of hepatocellular injury biomarkers (AST/ALT) in the NFOH group. These in vivo studies show the potential for NFOH as an effective and safe compound useful as an anti-T. cruzi agent.
Keywords: benznidazole; Chagas disease; chronic phase; hydroxymethylnitrofurazone; indeterminate form; Trypanosoma cruzi